Answer to Question #19092 in Mechanics | Relativity for john
Then, walking away with a speed v1,
d = v1*t = (1.1 m/s) * t, where if t is in s, d will be given to you in m.
Moving so for T = 60 seconds, the object will reach the distance of X = v1*T =
1.1 m/s * 60 s = 66 m.
Then turning around and moving towards the origin with the speed v2, the distance will be defined as
d = X - v2*t = 66 m - (6.0 m/s) * t.
d1 = v1*t = (1.1 m/s) * t;
d2 = X - v2*t = 66 m - (6.0 m/s) * t.
Need a fast expert's response?Submit order
and get a quick answer at the best price
for any assignment or question with DETAILED EXPLANATIONS!